دراسة وتصميم مرشح ضوئي عالي الانتقائية يعتمد على التوزع التجزيئي في تبدل قرينة الانكسار ضمن الليف الضوئي - صالح السموءل; صقور عفيف; خضور أصالة (Latakia University Journal -Engineering Sciences Series, 2018)
Recently, the studying of fiber bragg grating has attracted the attention, because it has characterized by a periodic structure in which a refractive index changes along the fiber. This structure doesnot pass all wavelengths and reflects the wavelength of bragg only [1][2]. It has been widely used in optical communication systems making various kinds of filters. On the other hand, the applications of fractals in the range of optical waves has attracted the attention, because it has characterized by a particular properties such as a property of self-similarity in which the parts of objects is exactly or approximately similar to object of itself ,but reduced by a reduction factor ,and the irregularity of the structure which leads to the appearance of the peaks inside high-attenuation frequency bands, this result lead to the hope in the design of many multi-frequency devices by applicate principle of the fractals on distribution of refractive indexes within optical fiber, for example, multi-band filters, selective filters wavelength ranging from (1000-3000)nm. تزايد الاهتمام في الفترة الأخيرة بدراسة الليف الضوئي المصنوع على هيئة شبكة براغ، حيث تتمتع الشبكة ببنية دورية تتبدل فيها قرينة الانكسار على طول الليف. لاتمرر هذه البنية جميع الأطوال الموجية حيث تعكس طول موجة براغ فقط. وقد استخدمت بشكل واسع في أنظمة الاتصالات البصرية لصنع مختلف أنواع المرشحات.[1][2] من ناحية ثانية فقد ازداد الاهتمام بالتطبيقات العملية للتوزع التجزيئي في مجال الأمواج الضوئية, كونه يملك خصائص فريدة مثل خاصية التشابه الذاتي، حيث كل جزء من الجسم التجزيئي يشبه الجسم الأصلي ولكن مصغر عنه بمقدار معامل التجزيء, إن عدم الانتظام الموجود في هذه البنية الذي ينتج عنه ظهور حزم تمرير (قمم) متوضعة ضمن حزم المنع الترددية, وهذه النتيجة تعطي أملاً في تصميم العديد من الأدوات متعددة الترددات بتطبيق مبدأ التوزع التجزيئي على تغيّر قرائن الانكسار ضمن الليف الضوئي, على سبيل المثال مرشحات متعددة الحزم, مرشحات انتقائية وذلك عند أطوال موجية تتراوح بين (1000nm,3000nm).